KURASHCHILARDA KO‘P YILLIK TAYYORGARLIK BOSQICHLARINI REJALASHTIRISH USLUBLARI - Karimov, X. (SCIENCE and SOCIETY, 2024)
The article pays special attention to the restoration of the national sport "Kurash". New methodical approaches have been analyzed to improving the system of training students engaged in wrestling, organizing the training process, choosing special training tools compatible with the traditions of the development of competition activities.
Keywords: wrestling; physical education; technical; sports; training; physical